ANALISIS PENILAIAN KINERJA KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN SUMBERASIH - Anam, Moh. Khoirul; Yunita Sari, Riska Nur (FKIP-Universitas Borneo Tarakan, 2024)
The type of research used in this study is a type of qualitative research, meaning that in qualitative descriptive research, where the data collected is not in the form of numbers but rather the data may come from interview scripts, field notes, personal documents, memos, and other official documents so that the purpose of this qualitative descriptive research is to describe and interpret objects according to what they are. This study aims to determine how the principal's performance is in managing the resources they have. Qualitative descriptive research is intended to describe and illustrate existing phenomena, both natural and human engineering, which pay more attention to the characteristics, quality, and interrelationships between activities. This research was conducted in 6 Elementary Schools in Sumberasih District, Probolinggo Regency. The reason for choosing this location is that the researcher wanted to know the performance of schools located on the border between Probolinggo City and Probolinggo Regency. The results of the study indicate that there needs to be an improvement in several aspects of the Principal's performance in an effort to motivate teacher performance. In improving the quality of education in schools, all elementary schools have made improvements to teachers by socializing the independent curriculum. Competency improvement is also carried out by involving teachers in KKG activities. This is done with the aim of motivating teachers to always understand the condition of students by implementing fun learning for students. Improving the school environment is carried out by the principal by involving the community in every school activity through coordination with the committee both in the quality of education and in facilities and infrastructure. The principal also asks for opinions and suggestions that can build on teachers and the surrounding community in order to improve school performance.